Systems and Circuits Linking Chronic Pain and Circadian Rhythms - Warfield, Andrew E.; Prather, Jonathan F.; Todd, William D. (Frontiers in Neuroscience, 2021)
Research over the last twenty years regarding the link between circadian rhythms and chronic pain pathology has suggested interconnected mechanisms that are not fully understood. Strong evidence for a bidirectional relationship between circadian function and pain has been revealed through inflammatory and immune studies as well as neuropathic ones. However, one limitation of many of these studies is a focus on only a few molecules or cell types, often within only one region of the brain or spinal cord, rather than systems-level interactions. To address this, our review will examine the circadian system as a whole, from the intracellular genetic machinery that controls its timing mechanism to its input and output circuits, and how chronic pain, whether inflammatory or neuropathic, may mediate or be driven by changes in these processes. We will investigate how rhythms of circadian clock gene expression and behavior, immune cells, cytokines, chemokines, intracellular signaling, and glial cells affect and are affected by chronic pain in animal models and human pathologies. We will also discuss key areas in both circadian rhythms and chronic pain that are sexually dimorphic. Understanding the overlapping mechanisms and complex interplay between pain and circadian mediators, the various nuclei they affect, and how they differ between sexes, will be crucial to move forward in developing treatments for chronic pain and for determining how and when they will achieve their maximum efficacy.